Legal Certainty Aspects of Securities as Debt Collateral in Lawsuit Processes - Dinda Seplinar Batubara; Keisyah Yuvi Amanda; Devani Agustia; M. Farhan Maulana; Fitra Ardiansyah (ISNU Sumatera Utara, 2025)
Securities play a strategic role in financial transactions as instruments that can be used as collateral for debt. However, in practice, issues arise regarding the legal certainty of securities in lawsuits, particularly when disputes arise between creditors and debtors. This study aims to examine the extent to which securities provide legal certainty in the process of enforcing creditors' rights through litigation. The research method used is a normative-juridical approach with an analysis of laws and regulations, jurisprudence, and legal doctrine. The results show that although securities such as checks and giro bills have the power to serve as evidence and collateral, their application in judicial practice still faces procedural obstacles and varying legal interpretations. Therefore, strengthening regulations and consistent legal application are needed to ensure legal certainty for the parties.